Discovering wine : a refreshingly unfussy beginner's guide to finding, tasting, judging, storing, serving, cellaring, and, most of all, discovering wine - Simon, Joanna (Mitchell Beazley, 2015)
Fresh, accessible, and gorgeous, this bestselling guide has been updated withthe latest information on wines in a visually stunning format. 30,000print.